The Effect Of Family Support On Postpartum Depression : Scoping Review - Navantri Muliyani; Endang Koni Suryaningsih (Indigenous: Jurnal Ilmiah Psikologi, 2023)
Abstract. Typically, a mother with postpartum depressive disorder is depressed and has suicidal thought. One of the factors that contributes to emotional stress is relationships with family. Mother's unstable emotions during the postpartum period may affect on the baby's growth besides the mother. Scoping review of existing scientific evidence on postpartum maternal mental health is the goal of this study. Using the Arksey and O’Malley's (2005) framework and the PRISMA-ScR checklist, this research applied a scoping review. In this study, PubMed, Science Direct, and ResearchGate were used for literature searches. The terms "support," "family," "parents," or "husband," and "mental health of postpartum mothers" were chosen as keywrods. Joana Briggs Institute (JBI) Appraisal Tool was implemented in this research. From 669 articles that could be utilized, 10 eligible articles were selected, those articles were written in English and published between 2019 until 2023. The articles focusing on the role of family support in postpartum mother’s mental health and containing conclusions about the effect of family support in postpartum mother’s mental health were all considered. This research was conducted in 7 distinct nations and each of the 10 eligible articles utilized a quantitative design. The mapping themes found are family support and satisfaction in relationships. The result of scoping review highlighted that the mother requires family support internally during the postpartum period. During the postpartum period, community-based health programs are effective in avoiding mental illness.